Morphological variation and taxonomy of Lepidocolaptes angustirostris (Vieillot, 1818) (Passeriformes: Furnariidae) - Leguizamón, Sergio David Bolívar (2014)
Lepidocolaptes angustirostris (Narrow-billed Woodcreeper) is a South American woodcreeper that inhabits predominantly open lowlands such as the Cerrado, Chaco and Caatinga. This species exhibits highly variable morphology and vocalization throughout its range. The taxonomic position of L. angustirostris is doubtful; it can be located in at the root or within the Lepidocolaptes genus radiation, depending on the author. Two main groups are recognized within the species, a northern clade distributed in the lowlands of northern Bolivia and central and northern Brazil, and a southern group, which inhabits northern and central Argentina, Uruguay and the state of Rio Grande do Sul, in Brazil. Eight subspecies are currently recognized based on plumage and geographical distribution patterns. However, a more detailed morphological analysis and taxonomic revision have not been conducted in this species. Based on the above information, the objective of this project is to conduct a taxonomic revision of L. angustirostris using morphometrical, plumage, and vocal characters. Second, with the aim to test the existence of phenotypic gradients associated to geographical and climatic variations in the taxon, a clinal and GLM analyses were performed. Finally, a distributional pattern was elaborated using geo-referenced records of examined individuals of the Narrow-billed Woodcreeper. The phenotypic analyses allowed us to identify six main plumage types; however, we also found a high level of intergradation among all of these populations. The PCA analyses show certain levels of morphological differentiation among the populations, with a first component correlated with bill characters (bill length, exposed and total culmen), and a second one that reflects the bill width and the tarsus-metatarsus length. These two components could explain 70.88% of the morphological variation described. Evidence of a latitudinal morphological variation was found, summarized in a series of clines partially overlapped on a region localized from the southern Cerrado and Pantanal ecoregions through the Humid and Dry Chaco and the Paraná Flooded Savanna, to the Espinal and Humid Pampas ecoregions. Some climatic variables explain the geographical variation in the taxon, mainly, temperature seasonality, annual precipitation, and minimum temperature of the coldest month. The ecogeographic rules of Bergmann and Gloger are consistent with this variation, as well as the Allens rule, but more narrowly. Thus, the populations of the Narrow-billed Woodcreeper tend to be larger to the south of the distribution. Due the intergradation of all populations found, with no clear diagnosable population, we propose here that Lepidocolaptes angustirostris be treated as a unique species with no subordinate taxa. Any evidence collected here did not support the taxonomic validity of the proposed subspecies in the Narrow-billed Woodcreeper. Despite colour-polymorphism identified in the plumage patterns, the high level of intergradation, the poor resolution of geographical boundaries, and the existence of clinal variation with a plausible introgression among populations not support the splitting of this species in several taxonomic subunits.